Easily Tunable Membrane Thickness of Microcapsules by Using a Coordination Assembly on the Liquid-Liquid Interface - Li, Bei-xing; Li, Xiao-xu; Liu, Yang; Zhang, Da-xia; Lin, Jin; Mu, Wei; Liu, Feng (Frontiers in Chemistry, 2018)
A model solvent, 1,3,5-trimethylbenzene, was encapsulated using coordination assembly between metal ions and tannic acid to reveal the deposition of coordination complexes on the liquid-liquid interface. The deposition was confirmed by zeta potential, energy dispersive spectroscopy and X-ray photoelectron spectroscopy. Scanning electron microscopy and transmission electron microscopy were integrated to characterize the microcapsules (MCs). According to atomic force microscopy height analysis, membrane thickness of the MCs increased linearly with sequential deposition. For MCs prepared using the Fe3+-TA system, the average membrane thicknesses of MCs prepared with 2, 4, 6 and 8 deposition cycles were determined as 31.3 ± 4.6, 92.4 ± 15.0, 175.4 ± 22.1 and 254.8 ± 24.0 nm, respectively. Dissolution test showed that the release profiles of all the four tested MCs followed Higuchi kinetics. Membrane thicknesses of MCs prepared using the Ca2+-TA system were much smaller. We can easily tune the membrane thickness of the MCs by adjusting metal ions or deposition cycles according to the application requirements. The convenient tunability of the membrane thickness can enable an extensive use of this coordination assembly strategy in a broad range of applications.